Congenital Kidney and Urinary Tract Anomalies: a Review for Nephrologists - Vieira, M (2021)
Kidney and urinary tract development disorder are two of the most prevalent congenital malformations and the main cause of chronic kidney disease in pediatric age patients. As such, it is very important that the neph‑ rologist understands these pathologies to improve transition and ensure a good continuity between pediatric and adult nephrological care. The purpose of this article is to present a brief review of congenital anomalies of the kidney and urinary tract (CAKUT). Kidney malformations are classified according to macroscopic and microscopic anatomic features, and are the result of the following abnormal renal developmental processes: malformations of the renal parenchyma, abnormalities of the embryonic migration of the kidneys and abnormalities of the developing urinary collecting system.